White cell and platelet content affects the release of bioactive factors in different blood-derived scaffolds. (4th July 2018) - Cabaro, S.; D'Esposito, V.; Gasparro, R.; Borriello, F.; Granata, F.; Mosca, G.; Passaretti, F.; Sammartino, J. C.; Beguinot, F.; Sammartino, G.; Formisano, P.; Riccitiello, F.
Abstract: Platelet-derived factors are biomaterials that might accelerate healing process in oral, maxillofacial, and several other applications. Release of specific factors by platelet concentrates is critical to achieving a successful outcome. Here, we have shown that platelet-rich fibrin (PRF) clots were beneficial sources of leukocytes, which may directly affect the release of chemokines and growth factors. When compared with the standard leukocyte-PRF (L-PRF), the experimental low-force modified procedure [defined as advanced-PRF (A-PRF)] entrapped the same content of viable leukocytes, released a similar amount of inflammatory cytokines, but secreted 3-, 1.6-, 3-, and 1.2-fold higher levels of Eotaxin, CCL5, platelet-derived growth factor (PDGF) and vascular endothelial growth factor (VEGF), respectively. A leukocyte-free scaffold, such as plasma rich in growth factors (PRGF), released only platelet-specific factors and, in particular, the F3 fraction, the richest in growth factors, secreted higher amount of CCL5 and PDGF compared to F1 and F2 fractions. In conclusion, different procedures and leukocyte content affect cytokine, chemokines, and growth factor release from platelet derivatives, which may be helpful in different clinical settings.